2013
DOI: 10.1155/2013/976035
|View full text |Cite
|
Sign up to set email alerts
|

The Age of Initiation of Drug Use and Sexual Behavior May Influence Subsequent HIV Risk Behavior: A Systematic Review

Abstract: Researchers examining injection drug users (IDUs) in drug treatment have been trying for decades to determine the optimal way to intervene to prevent the transmission and spread of human immunodeficiency virus (HIV) in this population. Although efficacious HIV risk reduction interventions are widely available, questions remain about what specific factors are most related to HIV risk behavior and defined as unprotected sexual activity and/or high risk drug use. This review involved an evaluation of the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 101 publications
4
27
0
1
Order By: Relevance
“…Consistent with previous findings from studies conducted in other countries or regions [8], we found that earlier anal sexarche was associated lack of condom use during anal sexarche and behaviors that conferred higher per contact risk of HIV infection (i.e., being the receptive or both the receptive and insertive partner) among our participants. In addition, earlier anal sexarche was associated with a range of current HIV-related risk behaviors including multiple sex partners, higher frequency of drug use, engagement in exchange sex, and inconsistent condom use with male partners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous findings from studies conducted in other countries or regions [8], we found that earlier anal sexarche was associated lack of condom use during anal sexarche and behaviors that conferred higher per contact risk of HIV infection (i.e., being the receptive or both the receptive and insertive partner) among our participants. In addition, earlier anal sexarche was associated with a range of current HIV-related risk behaviors including multiple sex partners, higher frequency of drug use, engagement in exchange sex, and inconsistent condom use with male partners.…”
Section: Discussionsupporting
confidence: 92%
“…One of such early sexual experiences that warrants more attention is earlier sexual debut (sexarche) and its co-occurring risk behaviors (i.e., sexual experiences during sexarche). A recent systematic review of 57 studies from diverse geographic locations and populations found that earlier initiation of sexual behavior was linked with higher levels of co-occurring health risk behaviors including unprotected intercourse [8]. Furthermore, results from these studies suggested that earlier sexarche might be associated with HIV risk behaviors at later points in life [8].…”
Section: Introductionmentioning
confidence: 99%
“…Age of opioid use initiation is a critical developmental concern, as those who initiate drug use at an earlier age are more likely to develop drug dependence problems (Anthony and Petronis, 1995; Baldwin et al, 2013; Chen et al, 2009; King and Chassin, 2007). Another milestone in the history of an opioid user is the transition from prescription opioids to injection heroin use.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Responden yang melakukan hubungan seksual sebelum menikah dilakukan dengan pasangannya (pacarnya) lebih dari 80%, sedangkan yang melakukan hubungan 19,20 Menurut penelitian Rico, menunjukan bahwa pengguna narkotika yang melakukan hubungan seksual pada umur ≤17 tahun berisiko 6,74 kali untuk melakukan perilaku seksual berisiko dibandingkan dengan yang melakukan hubungan seksual >17 tahun. 21 Perilaku seksual berisiko adalah melakukan hubungan seksual sebelum menikah, berganti-ganti pasangan dan tidak menggunakan alat kontrasepsi.…”
Section: Pembahasanunclassified